1977
DOI: 10.1126/science.196336
|View full text |Cite
|
Sign up to set email alerts
|

Rous Sarcomas in Chickens: Enhanced Growth Coexisting with Concomitant Immunity

Abstract: Chickens bearing Rous sarcoma virus-induced tumors in one wing did not develop new tumors when subsequently inoculated with Rous sarcoma virus in the other wing. However, the second inoculation of Rous sarcoma virus caused accelerated growth of the established tumors. This phenomenon was found to be bursa-dependent. Paradoxically, established tumors in bursectomized chickens grew at a diminished rate if the chickens were reinoculated with Rous sarcoma virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
10
2
Order By: Relevance
“…Thus, in neither of these latter two experiments did a second inoculation with RSV influence the growth of the initial tumor. These results are in contrast to those of McBride et al (1977) who found that primary tumor growth was enhanced following a second inoculation with RSV.…”
Section: Effect Of B Genotype Oncontrasting
confidence: 85%
See 4 more Smart Citations
“…Thus, in neither of these latter two experiments did a second inoculation with RSV influence the growth of the initial tumor. These results are in contrast to those of McBride et al (1977) who found that primary tumor growth was enhanced following a second inoculation with RSV.…”
Section: Effect Of B Genotype Oncontrasting
confidence: 85%
“…Immunity (as measured by resistance to induction of a second tumor) developed earlier in the regressor line, but by 15 days postinoculation (PI), chickens of both lines resisted a second challenge of either virus or tumor homogenate. McBride et al (1977) extended those findings to line G-Bl which is homozygous for the r-Rs-1 gene for progressive tumor growth (Schierman et al, 1977). All G-Bl chickens tested were resistant to a second challenge of RSV on the 8th day following primary inoculation.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations